1997
DOI: 10.1103/physrevlett.78.2732
|View full text |Cite
|
Sign up to set email alerts
|

High Energy Ion Explosion of Atomic Clusters: Transition from Molecular to Plasma Behavior

Abstract: We have studied the high-intensity femtosecond photoionization of inertially confined noble-gas clusters. The explosion of the resulting highly ionized, high-temperature microplasma ejects ions with substantial kinetic energy. We have observed Xe ions with kinetic energy up to 1 MeV and charge states as high as 40 1. This ion energy is over three orders of magnitude higher than has previously been observed in the Coulomb explosion of molecules or clusters of any kind and indicates that there is a fundamental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
117
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(120 citation statements)
references
References 18 publications
3
117
0
Order By: Relevance
“…The competing processes of evaporation and fission have been described by various liquid-drop models for clusters as diverse as atomic nuclei [42], multiply charged metal clusters [5,6], and highly charged solvent droplets [2,3]. The recent development of femtosecond lasers capable of rapidly ionizing many molecules in atomic or molecular clusters has permitted access to another dissociation process whereby a cluster undergoes a coulombic explosion, resulting in the isotropic ejection of many charged fragments [12][13][14][15].General characteristics of cluster dissociation are well illustrated by multiply charged metal clusters. Evidence for their dissociation was first observed by Sattler et al who, by measuring the mass and charge of Pb, Xe, and NaI clusters, observed half-integer cluster numbers that were interpreted to be doubly charged clusters [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The competing processes of evaporation and fission have been described by various liquid-drop models for clusters as diverse as atomic nuclei [42], multiply charged metal clusters [5,6], and highly charged solvent droplets [2,3]. The recent development of femtosecond lasers capable of rapidly ionizing many molecules in atomic or molecular clusters has permitted access to another dissociation process whereby a cluster undergoes a coulombic explosion, resulting in the isotropic ejection of many charged fragments [12][13][14][15].General characteristics of cluster dissociation are well illustrated by multiply charged metal clusters. Evidence for their dissociation was first observed by Sattler et al who, by measuring the mass and charge of Pb, Xe, and NaI clusters, observed half-integer cluster numbers that were interpreted to be doubly charged clusters [4].…”
mentioning
confidence: 99%
“…One motivation behind cluster research is that the transitional characteristics between bulk and molecular properties can be discovered by studying intermediate states of matter. Investigators have explored a wide variety of materials, including charged droplets of various liquids [2,3], clusters of noble metals [4][5][6][7][8], metal-ligand clusters [1,[9][10][11], highly charged clusters of noble gasses [12,13], small molecules [14,15], and ultracold clusters of transition metals [16]. Recently, investigators have formed noncovalently bound clusters of biologically important molecules, including clusters of amino acids and small peptides [17][18][19][20][21][22][23][24][25][26][27][28], and have studied their dissociation processes [18,20,[26][27][28].…”
mentioning
confidence: 99%
“…The experiments on laser interactions with atomic clusters have suggested that the laser-cluster interaction is more energetic than that of isolated atoms. Efficient generation of highly-charged atomic ions [1][2][3][4][5], generation of electrons and ions with MeV kinetic energies [4,[6][7][8], and emission of intense X-rays [2,9,10] were observed.…”
Section: Introductionmentioning
confidence: 97%
“…Experiments on clusters irradiated by the intense laser pulses have revealed efficient generation of extremely highly charged atomic ions [2][3][4][5][6][7][8] and generation of electrons and ions with MeV kinetic energies [6,7,[9][10][11]. Several other theoretical models have been proposed to explain the mechanism underlying the production of highly charged energetic ions in interaction of atomic clusters with intense laser pulses.…”
Section: Introductionmentioning
confidence: 99%